Changes in phytochemical synthesis, chalcone synthase activity and pharmaceutical qualities of Sabah snake grass (Clinacanthus nutans L.) in relation to plant age - Ghasemzadeh, Ali; Nasiri, Alireza; Jaafar, Hawa Z. E.; Baghdadi, Ali; Ahmad, Izham (MDPI, 2014)
In the current study, changes in secondary metabolite synthesis and the pharmaceutical quality of sabah snake grass leaves and buds were considered in relation to plant age (1 month, 6 months, and 1 year old). The activity of the enzyme chalcone synthase (CHS, EC 2.3.1.74) was measured, as it is a key enzyme for flavonoid production. Significant differences in total flavonoid (TF) production were observed between the three plant growth periods and the different plant parts. The highest contents of TF (6.32 mg/g dry weight [DW]) and total phenolic (TP) (18.21 mg/g DW) were recorded in 6-month-old buds. Among the flavonoids isolated in this study the most important ones based on concentration were from high to low as follows: catechin > quercetin > kaempferol > luteolin. Production of phenolic acids increased from 1 to 6 months, but after 6 months up to 1 year of age, they decreased significantly. The highest contents of caffeic acid (0.307 mg/g DW) and gallic acid (5.96 mg/g DW) were recorded in 1-year and 6-month-old buds, respectively. The lowest and highest activity of CHS was recorded in 1-month and 6-month-old buds with values of 3.6 and 9.5 nkat/mg protein, respectively. These results indicate that the increment in flavonoids and phenolic acids in 6-month-old buds can be attributed to an increase in CHS activity. The highest 1,1-diphenyl-2-picrylhydrazyl (DPPH) activity was observed in the extract of 1-year-old buds followed by 6-month-old buds, with 50% of free radical scavenging (IC50) values of 64.6 and 73.5 µg/mL, respectively. Interestingly, a ferric reducing antioxidant power (FRAP) assay showed a higher activity in 6-month-old buds (488 μM of Fe(II)/g) than in 1-year-old buds (453 μM of Fe(II)/g), in contrast to the DPPH result. Significant correlations (p < 0.05) were observed between CHS enzyme activity and FRAP activity, TF, catechin, and kaempferol content. Extracts of 6-month-old bud exhibited a significant in vitro anticancer activity against HeLa cancer cells with IC50 value of 56.8 µg/mL. These results indicate that early harvesting of snake grass (6-month-old) may yield increased concentrations of secondary metabolites, which are potent antioxidant compounds.